Modifikasi Aspal Dengan Limbah Plastik LDPE Yang Diolah Dengan Inisiator Glacidyl Methacrylate Dan Benzoil Peroksida - Yolandha Putri; Tamrin Tamrin; Darwin Yunus Nasution (Postgraduate, University of Mataram, 2023)
The aim of this research is to determine the quality of the softening point test, penetration test and deactivation of modified asphalt from garfted LDPE plasticization waste. And for grafting treatment, use the internal mixer method where GMA and BPO are added to the grafting mixture. From the grafting results obtained, we carried out an FTIR test and identified a wave number of 1728/cm indicating the presence of the C-H or benzene functional group. This can be interpreted as a grafting process which can also be seen at the wave number 1730/cm. This can be interpreted as a grafting process from GMA to LDPE. And for the wave number at 2723/cm, there is a CH3 stetching from the LDPE chain backbone so that what is obtained is the LDPE-g-GMA spectrum. As for the TGA and DSC test results obtained, namely that in DSC the peak value of the number is at a temperature of 160.60 C and the value obtained from TGA is 373.13 C. And to find out the standard of modified asphalt from mixing asphalt with waste The value of the grafted plastic that we carried out was 65.23, for the penetration test it was 53.7 and for the deactivation test it was 55.46. This can be interpreted that all three are in accordance with the 2018 Bina Marga asphalt standards